Avaliação do desempenho de diferentes métodos no diagnóstico laboratorial da leishmaniose visceral humana - Fonseca, Giuliana Schmidt França (2013)
The routine diagnosis of human visceral leishmaniasis (VL) is usually based on clinical and epidemiologic parameters associated to parasitological and/or immunological tests. Being a fatal disease if not treated, the search for more effective, easy to perform, simple, affordable, and fast diagnostic methods, is necessary, decreasing the time to obtain results. Therefore, in this study the performance of different methods already used in the routine or proposed as alternative tools to the diagnose of VL was evaluated, which included the direct parasite detection (DPD) on bone marrow aspirates, indirect immunofluorescent assay (IFA), rK39 rapid test (Kalazar Detect®), ELISA test using L.chagasi soluble antigen, and immunofluorescence by flow cytometry (FC-AFPA). Seventy-seven biological specimens (bone marrow and serum) from patients with clinical diagnosis of VL, treated, and cured were assessed. The sensitivity of evaluated tests was 48% for DPD, 74% for IFA, 79% for rK39 rapid test, 88% for ELISA-SLA, and 94% for FCAFPA. The comparative analysis demonstrated higher concordance among serological tests in comparison to serological tests and DPD, due to the low sensitivity of the latter. It was also done the comparison between the results of serological tests and direct examination. However, our results showed that the performance of tests was similar regardless of DPD results. In addition, our study evaluated the performance of two algorithms for the diagnosis of VL based only on serological tests. The first of them using IFA as a initial test, since this is the test provided by the Ministry of Health (MH) for reference laboratories for diagnosis of VL, and a second algorithm using the rK39 rapid test, that has recently been suggested as a screening test by the MH. It was demonstrated that the algorithm presenting the best performance, that is, all the cases were detected, was the one using rapid test as initial test followed by FC-AFPA.